2009
DOI: 10.1007/s00210-009-0477-x
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin increases phagocytosis and acidifies lysosomal/endosomal compartments in AMPK-dependent manner in rat primary microglia

Abstract: Recent evidence suggests that metformin shows beneficial effects in experimental models of neuroinflammatory diseases. The aim of the present study was to determine the effect of metformin on phagocytosis and acidification of lysosomal/endosomal compartments in rat primary microglia in the presence of lipopolysaccharide (LPS) and/or beta-peptides (25-35), (1-40), and (1-42). Metformin increased the phagocytosis of fluorescent microspheres in the presence or absence of all the beta-peptides. However, the drug h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…Our results showed that AMPK activation effectively no adverse effects on bacterial killing by neutrophils or macrophages ex vivo. Of note, activation of AMPK has been shown to increase phagocytosis in neutrophils and macrophages (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that AMPK activation effectively no adverse effects on bacterial killing by neutrophils or macrophages ex vivo. Of note, activation of AMPK has been shown to increase phagocytosis in neutrophils and macrophages (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that activated AMPK can also modulate the resolution of inflammatory conditions due to enhancement of the phagocytic ability of macrophages and neutrophils. In particular, AMPK activation increased the uptake of bacteria and enhanced efferocytosis, an essential process in the resolution of inflammation in which apoptotic cells are ingested and cleared by phagocytic cells (39,59,60). Beneficial effects of AMPK activation also were related to improvement of vascular integrity in mice models for endotoxemia-induced ALI and to airway remodeling in asthma (34,61).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were washed three times with PBS to remove nonphagocyted spheres, and cells were fixed in 4% PFA for 15 min. Phagocytosis was quantified counting both the number of phagocyting cells (scoring as positive only cells with at least three FluoSpheres; Labuzek et al, 2010) and the number of red FluoSpheres per cell in at least 10 random fields for coverslip (594 nm, Axioscope 2; Carl Zeiss).…”
Section: Phagocytosis and Elisasmentioning
confidence: 99%